2000
DOI: 10.1074/jbc.m910354199
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Mutagenesis of Transmembrane Segments 4 and 5 of the Tn10-encoded Metal-Tetracycline/H+ Antiporter Reveals a Permeability Barrier in the Middle of a Transmembrane Water-filled Channel

Abstract: Cysteine-scanning mutants as to putative transmembrane segments 4 and 5 and the flanking regions of Tn10-encoded metal-tetracycline/H ؉ antiporter (TetA (B)) were constructed. All mutants were normally expressed. Among the 57 mutants (L99C to I155C), nine conserved arginine-, aspartate-, and glycine-replaced ones exhibited greatly reduced tetracycline resistance and almost no transport activity, and five conserved glycine-and proline-replaced mutants exhibited greatly reduced tetracycline transport activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 39 publications
(57 reference statements)
3
46
0
Order By: Relevance
“…Tet(L) G155C or S retained a modest capacity to confer resistance in the absence of Tc-Co 2+ efflux activity, just as Iwaki et al (23) found for the similarly located G145C mutation of TetA(B) G145C. It is not known whether these findings represent an effect of these mutant Tet proteins on the E. coli host (e.g.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Tet(L) G155C or S retained a modest capacity to confer resistance in the absence of Tc-Co 2+ efflux activity, just as Iwaki et al (23) found for the similarly located G145C mutation of TetA(B) G145C. It is not known whether these findings represent an effect of these mutant Tet proteins on the E. coli host (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…As with Tet(L) G155C, de-energized control vesicles in transport assays of the TetA(B) G145C mutation (the equivalent position to Tet(L) G155 in the 12-TMS Tc-Me 2+ /H + antiporter) as well as mutants in two other Motif C Gly residues of TetA(B), showed elevated binding compared to controls for other mutants (23). Tet(L) G155C or S retained a modest capacity to confer resistance in the absence of Tc-Co 2+ efflux activity, just as Iwaki et al (23) found for the similarly located G145C mutation of TetA(B) G145C.…”
Section: Discussionmentioning
confidence: 99%
“…The spacing between the Gly residues is equivalent to one turn of a helix, indicating a possible structural role. Indeed, Ala or Cys mutants of the second Gly in this motif in TM5 decrease transport activity in some members of the DHA12 family (22,23). Interestingly, in our alignment, motifs in TMs 5 and 11 of rVMAT2 align to Gly-rich segments in the LacY sequence, even though LacY belongs to a different family from the DHA12 proteins.…”
Section: Resultsmentioning
confidence: 88%
“…It is likely that Gly-313 may assume a structurally important role that is required for the function of QacA rather than being directly involved in substrate binding. This is commonly seen (10,25,26), as Gly occurs frequently in the TMS of membrane proteins and is often found in interhelical positions (27) that play important roles in mediating interactions between helices (28,29). The lack of a side chain allows Gly to form close interhelical contacts and provides a good packing surface (30); Gly can also be either the donor or acceptor of an interhelical C-H⅐⅐⅐O hydrogen bond that may contribute to the stability of interhelical interactions (31).…”
Section: Discussionmentioning
confidence: 99%